Designing an activity application for people with cognitive disabilities: What should be considered when designing a UI for people with cognitive disabilities? - Janebäck, Johanna; Jonsson, Ella (My University, 2020)
This master thesis project treats the topic of user interface and user experience design, developed for people with cognitive impairment. The project has been carried out at the request of the non-profit association Grunden in Göteborg. Grunden has requested a user study and prototype of a smartphone application interface for an application that is to promote independence in everyday life for the target group. The application will be used by the target group to find activities to attend, and thereby increasing their opportunity to be independent and to take charge of their own everyday life. The research question of this project is: What should be considered when designing a UI for people with cognitive disability? To answer this question, a literature study was firstly conducted. From this study, general accessibility guidelines were found along with methods and knowledge about how to best work with this particular target group. After the literature study, initial interviews were held at Grunden with several people of the target group. Following these interviews, a thematic analysis was made to pinpoint themes and important aspects found in the interviews. Some questions arose after the analysis, and more interviews were held to answer them. The questions were rather specific and regarded the expected and desired functionality of the application. All data gathered up to this point was compiled in to a requirement specification. Using the requirements specification, an initial prototype of the application was made using Figma. This prototype was then tested with several people of the target group. Any issues or opinions expressed by or seen in the target group during the tests was then remedied or adapted in the prototype. The project continued this way for approximately seven weeks, creating many iterations of the prototype. During some tests, a specific function was tested, and other tests treated the prototype as a whole. During tests and interviews, it became increasingly clear what works better in terms of UI design for this target group. Some important factors include using simple language, follow WCAG or corresponding accessibility guidelines, make navigation sequential and avoid giving to much information on a single page. For future work, it is recommended that researchers or designers evaluate the concept with more people of the target group, preferably people outside of the association Grunden, since all of the interviewees and testers have been members of Grunden.
Keywords: user experience design; user interface design; accessibility; engineering; project; thesis